Discombobulations and Transitions: Using Blogs to Make Meaning of and From Within Liminal Experiences. (December 2017) - MacLaren, Jessica; Georgiadou, Lorena; Bradford, Jan; Taylor, Liz
We live in a digitalized world, where social media have become an integral part of scholarly life. Digital tools like blogs can facilitate various research-related activities, from recruitment, to data collection, to communication of research findings. In this article, we analyze our experience of blogging to suggest that they provide a useful resource for qualitative researchers working with reflexive accounts of personal experience. Through our personal story of engaging with blogging while traveling abroad to participate in a conference, we explore how we used the blog in different ways to concretize transitional processes, to engage in public storytelling, and to form a network of relationships (self, others, and blog). We argue that the technology of blogging is particularly suited to creating sense-making narratives from liminal or discombobulating experiences, and highlight the usefulness of understanding the production of data through blogging as culturally located within networks of relationships and normative discourses.